1998
DOI: 10.1111/j.1469-7998.1998.tb00076.x
|View full text |Cite
|
Sign up to set email alerts
|

Sperm fertility and skewed paternity during sperm competition in the Australian long‐eared bat Nyctophilus geoffroyi (Chiroptera: Vespertilionidae)

Abstract: Prolonged sperm storage, rare among mammals, is widespread among bats and may promote sperm competition, assuming stored sperm are fertile. However, while sperm storage has been documented in many bat species, there have been few investigations of the fertility of stored sperm. Related to this, and a fundamental question in the study of competition at the gametic level, is the effect of mating order on success during sperm competition. For mammals there are no clear mating order effects, in part because female… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Spring swarming could also occur if there are advantages for males in late matings through sperm competition (Fenton 1984;Watt and Fenton 1995;Hosken 1998) or by increased fertilization success in females. Hosken (1998) found out superior males of the less long-eared bat (Nyctophilus geoffroyi Leach, 1821) during sperm competition.…”
Section: Autumn and Spring Swarming Behaviourmentioning
confidence: 98%
See 1 more Smart Citation
“…Spring swarming could also occur if there are advantages for males in late matings through sperm competition (Fenton 1984;Watt and Fenton 1995;Hosken 1998) or by increased fertilization success in females. Hosken (1998) found out superior males of the less long-eared bat (Nyctophilus geoffroyi Leach, 1821) during sperm competition.…”
Section: Autumn and Spring Swarming Behaviourmentioning
confidence: 98%
“…Hosken (1998) found out superior males of the less long-eared bat (Nyctophilus geoffroyi Leach, 1821) during sperm competition. Senior et al (2005) demonstrated mating to be skewed towards males that roost with females in summer and Watt and Fenton (1995) found reproductive success to be skewed in swarming M. lucifugus.…”
Section: Autumn and Spring Swarming Behaviourmentioning
confidence: 99%
“…Where males compete with each other for access to females, large body size often confers an advantage and thus correlates positively with individual paternity success [1] . High variance in breeding success among individuals leads to reproductive skew at the population level, which has been shown in a range of mammalian groups including ungulates [2] , primates [3] , pinnipeds [4] , carnivores [5] and bats [6] . In addition to size, other sources of variation (some correlated with size) may also influence a male's access to females, such as whether he holds a high quality territory [7] , his age [8] and his level of heterozygosity [9] .…”
Section: Introductionmentioning
confidence: 99%